If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 34 = -36 Reorder the terms: 34 + 6x = -36 Solving 34 + 6x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-34' to each side of the equation. 34 + -34 + 6x = -36 + -34 Combine like terms: 34 + -34 = 0 0 + 6x = -36 + -34 6x = -36 + -34 Combine like terms: -36 + -34 = -70 6x = -70 Divide each side by '6'. x = -11.66666667 Simplifying x = -11.66666667
| -0.7X+5.85=-0.5X+8.25 | | 4(3x-4)=2(3x+1) | | (20x+4)=(6x+4) | | 10.410= | | 3x(2-2x)=-6x(x-1) | | 2w-54=-w+21 | | 7a+4=4a | | 2=5y-3 | | H=16t^2+352t | | 15x-9=3x+2 | | (8x+18)=(6x+4) | | F=1/2gq | | 5-3s=-s-5 | | 3n-21=2n | | 8x+18=6x+4 | | 5+4v=29 | | 8x+2-3=1 | | 3x-1=77 | | 0p+9-11-p=2(2p+4)-3(2p-2) | | 2v+5=4u+13 | | 126=-9(4+r) | | 2p+9=3p-6 | | p-12=34+q | | Y-18=x+5 | | 3p=7(9p+2) | | 3(6x+2)=30 | | 4x-2(x-3)=-9+5x-9 | | 13.3+7u=-4.2 | | 7+5p=6p | | 7+5(2x+3)-9= | | 3x+8x-2=108 | | 27=3u-15 |